2018
DOI: 10.1051/0004-6361/201833626
|View full text |Cite
|
Sign up to set email alerts
|

Updated astrometry and masses of the LUH 16 brown dwarf binary

Abstract: The nearest known binary brown dwarf WISE J104915.57-531906.1AB (LUH 16) is a well-studied benchmark for our understanding of substellar objects. Previously published astrometry of LUH 16 obtained with FORS2 on the Very Large Telescope was affected by errors that limited its use in combination with other datasets, thereby hampering the determination of its accurate orbital parameters and masses. We improve upon the calibration and analysis of the FORS2 astrometry with the help of Gaia DR2 to generate a high-pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Our mass of 67 +4 −5 M Jup for the T3.5 2M1059−21B is also significantly higher than its two spectral type equivalents DENIS J2252−1730B (T3.5, 41 ± 4 M Jup ) and 2MASS J1534−2952A (T4.5, 51 ± 5 M Jup ). Sahlmann (2018), andDupuy et al (2019). The curves correspond to isochrones of different ages (0.3, 0.5, 1, 5, and 12 Gyr; Baraffe et al 2015), where we used the spectral type -effective temperature calibrations of Houdebine et al (2019) for M dwarfs and of Stephens et al (2009) for L and T dwarfs to convert theoretically predicted effective temperatures into spectral types.…”
Section: Masses Of T Dwarf Companionsmentioning
confidence: 99%
“…Our mass of 67 +4 −5 M Jup for the T3.5 2M1059−21B is also significantly higher than its two spectral type equivalents DENIS J2252−1730B (T3.5, 41 ± 4 M Jup ) and 2MASS J1534−2952A (T4.5, 51 ± 5 M Jup ). Sahlmann (2018), andDupuy et al (2019). The curves correspond to isochrones of different ages (0.3, 0.5, 1, 5, and 12 Gyr; Baraffe et al 2015), where we used the spectral type -effective temperature calibrations of Houdebine et al (2019) for M dwarfs and of Stephens et al (2009) for L and T dwarfs to convert theoretically predicted effective temperatures into spectral types.…”
Section: Masses Of T Dwarf Companionsmentioning
confidence: 99%
“…The mass and radius inferred using two different models for CO (ExoMol using the ".broad" file and HITEMP2019). The astrometric mass is shown in the blue shaded region (Lazorenko & Sahlmann 2018). The dashed lines show the iso-gravity lines.…”
Section: Summary and Limitationmentioning
confidence: 99%
“…Even though it is predicted that the Li I resonance doublet could remain strong down to Teff = 500 K (Burrows et al 2002), this feature has not yet been observed at spectral type later than T3.5±0.5 (this work), and thus we limit our study to objects not later than T3±1.0, corresponding to Teff about 1100 K. The relevant information available in the literature for the sample of seven VLM binaries that meet our criteria, together with that for Sahlmann 2 AB and Reid 1 AB, are summarized in Table 2. Two of the binaries, namely Epsilon Indi Ba,b, and Luhman 16 AB, are the two closest substellar systems to the Sun, they have dynamic mass measurements (Dupuy et al 2019;Lazorenko & Sahlmann 2018), and they have spatially resolved optical spectra of the individual components with sufficient quality to detect the Li I resonance doublet. It is indeed detected in both components of Luhman 16 AB (Faherty et al 2014;Lodieu et al 2015b), but not in the components of Epsilon Indi B (King et al 2010).…”
Section: Lithium In the Individual Components Of Vlm Binaries From Th...mentioning
confidence: 99%